Evolution of emergency management in Malaysia - Aini, Mat Said; Fakhru’l‐Razi, Ahmadun; Daud, Mohamed (Wiley, 2001)
Various types of disaster ranging from biological, structural collapse, fire and explosion, landslides and meteorological incidents have struck Malaysia. Safety and emergency laws and regulations in Malaysia had evolved in pace with the development and industrialisation of the country. Some of these disasters were land-marked disasters whereby various safety and emergency acts and regulations were amended or introduced. In this article, the history of the evolution of various Safety and Emergency Laws, Regulations and Acts in the country since independence in 1957 until the establishment of the Permanent Guidelines for Disaster Management and Relief Operations in 1997 is presented. Lessons from past disasters and the rapid expansion of industrialisation have greatly influenced the evolution of safety and emergency management in Malaysia. However, this intermediary phase in the pursuit of development is often accompanied by an increase in vulnerability (McEntire, 1997). This paper discusses reasons that are attributed to the increase in vulnerability as well as the challenges faced by the nation in the area of safety and emergency planning.